The Role of Streptococcus mutans Virulence Proteins in the Pathogenesis of Endocarditis: Mechanisms of Action and Impact on Heart Infections, A Review - Winato, Brigad Mahardika; Mylano, Tri Adi (Journal of Syiah Kuala Dentistry Society, 2024)
Background: Streptococcus mutans, known for causing dental caries, can also lead to endocarditis, a severe heart infection involving inflammation of the heart's inner lining and valves. This study focuses on the virulence proteins of Streptococcus mutans and their role in endocarditis pathogenesis. Objective: To investigate the mechanisms of action of Streptococcus mutans virulence proteins and their impact on the development of endocarditis. Methods: A comprehensive literature review focused on the virulence factors of Streptococcus mutans, such as Glucosyltransferases (Gtf), Adhesin P1 (Antigen I/II), Dextranase, and proteolytic enzymes. The role of these proteins in bacterial adhesion, biofilm formation, and tissue invasion was analyzed. Results: Glucosyltransferases facilitate biofilm formation by synthesizing sticky glucans from sucrose, protecting bacteria, and aiding the colonization of heart valves. Adhesin P1 enables bacterial attachment to host tissues, which is crucial for initial colonization. Dextranase modifies biofilm structure, enhancing stability and resistance. Proteolytic enzymes degrade host proteins, aiding bacterial invasion and causing tissue damage. Conclusion: Streptococcus mutans employ multiple virulence proteins to adhere to, colonize, and invade heart tissues, leading to endocarditis. Understanding these mechanisms is essential for developing preventive and therapeutic strategies against this severe infection.